ANALISIS PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, TRANSAKSIONAL, DAN DEMOKRATIS TERHADAP KOMITMEN ORGANISASI KEPEMUDAAN PPGT DI KLASIS MAKASSAR TIMUR - Aljun; Baharuddin; Agustinus (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study aims to analyze the effects of transformational, transactional, and democratic leadership styles on organizational commitment within PPGT youth organizations in the East Makassar Klasis. The study is based on the importance of leadership's role in shaping members' commitment to an organization, particularly in the context of voluntary, participatory youth organizations. The study employed a quantitative approach with a survey method. The population consisted of active PPGT members in the East Makassar Klasis, and the sample size was 100 respondents, who were selected using a random sampling technique. The instrument used was a questionnaire based on indicators of each variable. Multiple linear regression was used to analyze the data and determine the simultaneous and partial effects of each leadership style on organizational commitment. The results showed that transformational, transactional, and democratic leadership styles had a significant simultaneous effect on organizational commitment. Transformational leadership style was found to be partially significant to organizational commitment. Democratic leadership style was also found to affect organizational commitment, while transactional leadership style was found to have a lower, yet still significant, effect